Screening of Antiviral Components of Ma Huang Tang and Investigation on the Ephedra Alkaloids Efficacy on Influenza Virus Type A - Wei, Wenyang; Du, Haixia; Shao, Chongyu; Zhou, Huifen; Lu, Yiyu; Yu, Li; Wan, Haitong; He, Yu (Frontiers in Pharmacology, 2019)
Although Ma Huang Tang (MHT) has long been considered as a classical formula for respiratory infections like influenza, bronchitis and asthma, its chemical ingredients really exert the antiviral efficacy are still obscure. In this study we aimed to screen its antiviral components and investigate the potential mechanisms. The MDCK cellular research results showed that, among nine predominant ingredients of MHT, L-methylephedrin (LMEP), L-ephedrine (LEP), D-pseudoephedrine (DPEP) significantly inhibited the proliferation of influenza A virus in vitro, and the inhibitory effect at 24 h after the treatment was more obvious than that at 48 h. They also significantly inhibited the mRNA expression levels of related genes in TLR3, TLR4 and TLR7 signaling pathways, which accompanied with the down-regulation of TNF-α level and the up-regulation of IFN-β level in the cell supernatant. Therefore, three Ephedra alkaloids exert antiviral effect in vitro which may be closely related to the inhibition of viral replication and the modulation of inflammatory response. Animal research further indicated, at the 3rd and 7th days after infection, LEP and DPEP significantly attenuated lung injury, decreased lung index, virus load in the lung and the level of IL-1β in serum, inhibited the mRNA expression levels of TNF-α, TLR3, TLR4, TLR7, MyD88, NF-κB p65 and RIG-1 as well as the protein expression levels of TLR4, TLR7, MyD88 and NF-κB p65, markedly increased thymus index, the level of IL-10 in serum and the mRNA expression level of IFN-γ. LEP and DPEP have certain protective effects on the influenza virus-infected mice, which may be associated with their abilities of effectively alleviating lung injury, improving the immunologic function of infected mice and adjusting the host's TLRs and RIG-1 pathway. The overall findings demonstrate that, as the effective and inexpensive natural substances, Ephedra alkaloids and MHT may have potential utility in the clinical management.